2020
DOI: 10.2139/ssrn.3551626
|View full text |Cite
|
Sign up to set email alerts
|

A Poisson Autoregressive Model to Understand COVID-19 Contagion Dynamics

Abstract: We present a statistical model which can be employed to understand the contagion dynamics of the COVID-19. The model is a Poisson autoregression, and can reveal whether contagion has a trend, and where is each country on that trend. Model results are presented from the observed series of China, Iran, Italy and South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…Agosto and Giudici [2] drew a similar conclusion from their analysis of the Chinese data, which covers the period from January 20 to March 15, 2020. Their estimated β and γ parameters (final column of Table 1) revealed that the contagion cycle was in a downward trend (γ < β).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Agosto and Giudici [2] drew a similar conclusion from their analysis of the Chinese data, which covers the period from January 20 to March 15, 2020. Their estimated β and γ parameters (final column of Table 1) revealed that the contagion cycle was in a downward trend (γ < β).…”
Section: Resultsmentioning
confidence: 67%
“…Poisson autoregressive as a function of a short-term dependence only 2. Poisson autoregressive as a function of both a short-term dependence and a long-term dependence Following Agosto and Giudici [2], the number of new cases yt reported at time (day) t is assumed to follow a Poisson distribution i.e. yt ~ Poisson (λt), with a log-linear autoregressive intensity specification, as follows:…”
Section: Data Sourcementioning
confidence: 99%
“…For notational convenience, we will omit the subscript i for the remainder of this section. We sample the joint posterior distribution for θ = [α 0 , α, β, γ, δ, η, n, κ], p(θ | D) ∝ p(D | θ)p(θ), (1) where p(D | θ) is the likelihood function and p(θ) is the prior distribution. The likelihood function is intractable, due to the unobserved populations S t , I t , and R u t .…”
Section: Bayesian Analysismentioning
confidence: 99%
“…A variety of modelling strategies have been applied. Techniques include: empirical approaches such as phenomenological growth curves [29]; data-driven, statistical approaches using non-linear autoregressive models [31]; and mechanistic models based on epidemiological theory [32] with various extensions [33,34].…”
Section: Introductionmentioning
confidence: 99%